Investigating the Demand of Small Hotel and Restaurant Businesses for Bank Financing: The Case of Turkey - Erdogan, Aysa Ipek (Journal of Empirical Studies, 2016)
The literature argues that small businesses are highly dependent on bank financing due to their inability to access the capital markets. We paint a different picture in this paper that analyzes the demand of small hotel and restaurant businesses for bank financing in Turkey. The results of a countrywide survey done with the owners/managers of the businesses that were responsible for the financial affairs are used for the analysis. We find that the majority of the businesses in the sample did not make a loan application in the last three years. Moreover, the tendency of firms to apply for bank financing did not change with age. When asked whether their firm were in a position not to apply for a bank loan in the last three years even if they needed bank financing with the idea that the application would be rejected, nearly all the participants responded negatively. The majority of the owners/managers of the firms declared that their firm’s demand for bank loans would increase with lower interest rates and lower collateral requirements. On the other hand, firms that would have a higher demand for bank loans if there were a reduction in interest rates and collateral requirements were younger firms.